Insomnia and left ventricular function – an echocardiography study. (3rd May 2016) - Strand, Linn B.; Laugsand, Lars E.; Dalen, Håvard; Vatten, Lars; Janszky, Imre
Abstract: Objectives . Recently, studies have reported an association of insomnia with incident heart failure but its causal relation is still uncertain. In patients with heart failure, the left ventricular function is impaired and the deterioration may start long before the patient experiences any symptoms. As the first study, we examined the association of insomnia with left ventricular function using state-of-the art echocardiography methods. Design . In the echocardiography study, several indices of left ventricular function were examined in participants free from cardiovascular diseases, hypertension and diabetes. In total 788 participants with information on all relevant covariates were included. We calculated the least square mean of indices of left ventricular function associated with increasing number of insomnia symptoms (i.e. difficulties falling asleep, frequent awakenings and early awakenings), including systolic mitral annular excursion, peak velocities of systolic and diastolic motion of the mitral annulus and systolic deformation of the left ventricle. Results . We found no clear evidence that increasing number of insomnia symptoms is associated with any of the left ventricular function indices. Conclusions . The methods that were used are sensitive to detect preclinical HF, and therefore, our findings do not support a causal relation between insomnia symptoms and HF.